Penerapan metode edutainment berbasis guided discovery learning (GDL) untuk meningkatkan keterampilan menyimpulkan pada pembelajaran IPA kelas iii sekolah dasar - Rizky Nurdianti; Idam Ragil Widianto Atmojo; Sularmi Sularmi (Didaktika Dwija Indria, 2020)
Abstract. This research aims to improve the concluding skills in natural science learning using Edutainment methods based on Guided Discovery Learning (GDL). The type of research is classroom action research. The subject of the research were the 3rd grade student of SD N Kerten II No. 243 Surakarta in the 2019/2020 academic year, totalling 12 student. Data collection techniques using observation, interviews, concluding skills test, and documentation. Data validity techniques using content validity and triangulation. Data analysis techniques using the interactive analysis model of Miles-Huberman. The result showed the percentage of the first indicator of the pre-cycle stage was 0,00%, increased in the first cycle to be 45,45%, and increased in the second cycle to be 91,67%. The percentage on the second indicator shows the pre-cycle stage was 0,00%, increased in the first cycle to be 27,27%, and increased in the second cycle to be 100%. Based on the result of the study, it can be concluded that the implementation of edutainment method based on guided discovery learning can improve the concluding skills of natural science learning in 3rd grade students of SD N Kerten II No. 243 Surakarta in the academic year 2019/2020.